2022
DOI: 10.3390/ijerph19031753
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Calcitonin Gene-Related Peptide (CGRP) Monoclonal Antibodies for the Preventive Treatment of Migraine: A Protocol for Multiple-Treatment Systematic Review and Meta-Analysis

Abstract: Background: Migraine is a common and disabling primary headache disorder, associated with many medical comorbidities, highly prevalent, with complex treatment and management. Currently, monoclonal antibodies targeting the trigeminal sensory neuropeptide, calcitonin gene-related peptide (CGRP), are available. The aim of this protocol is to provide a review comparing the effects and safety profile of different monoclonal antibodies in migraine patients. Methods: The literature search will be performed through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The findings of this study also show their long-term safety, making them a valuable option for migraine prevention. Fernández-Bravo-Rodrigo et al (2022) also revised a similar study and supported the findings of Vandervorst et al (2021) [ 15 , 6 ]. This study utilizes meta-analytical methods to provide comprehensive evidence on the efficacy and safety of different CGRP monoclonal antibodies for the treatment of migraine [ 39 ].…”
Section: Reviewsupporting
confidence: 68%
See 2 more Smart Citations
“…The findings of this study also show their long-term safety, making them a valuable option for migraine prevention. Fernández-Bravo-Rodrigo et al (2022) also revised a similar study and supported the findings of Vandervorst et al (2021) [ 15 , 6 ]. This study utilizes meta-analytical methods to provide comprehensive evidence on the efficacy and safety of different CGRP monoclonal antibodies for the treatment of migraine [ 39 ].…”
Section: Reviewsupporting
confidence: 68%
“…It has also been shown to be well-tolerated, with few adverse effects [ 14 ]. Fremanezumab and galcanezumab are humanized monoclonal antibodies that target CGRP itself [ 15 ]. Clinical trials have shown that these drugs reduce the number of patients suffering from migraines by up to 50% or more in approximately 50%-60% of individuals with migraines [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there are no data about head-to-head comparison between distinct anti-CGRP mAb, so primary studies will also be needed to improve the evidence-based data. During the elaboration of this review, a protocol to perform a systematic review and meta-analysis comparing the effects and safety profile of different monoclonal antibodies in migraine patients has been published, meaning that this issue is getting increasing interest from researchers to create evidence for clinical practice recommendations although these studies, in particular, do not target solely resistant chronic migraine [ 87 ].…”
Section: Discussionmentioning
confidence: 99%